2014
DOI: 10.2337/dc13-1901
|View full text |Cite
|
Sign up to set email alerts
|

Second-Line Agents for Glycemic Control for Type 2 Diabetes: Are Newer Agents Better?

Abstract: OBJECTIVEWhile metformin is generally accepted as the first-line agent in treatment of type 2 diabetes, there are insufficient evidence and extensive debate about the best second-line agent. We aimed to assess the benefits and harms of four commonly used antihyperglycemia treatment regimens considering clinical effectiveness, quality of life, and cost. RESEARCH DESIGN AND METHODSWe developed and validated a new population-based glycemic control Markov model that simulates natural variation in HbA 1c progressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
52
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 34 publications
0
52
0
1
Order By: Relevance
“…Another analysis performed on 39 randomized controlled trials involving 17 860 individuals, showed that glucagon-like peptide-1 (GLP-1) analogues led to a greater decrease in HbA1c compared with SUs, glinides, thiazolidinediones, α-glucosidase inhibitors and DPP-4 inhibitors [75]. Aiming to assess the benefits and harms of commonly used antihyperglycaemic treatment regimens, Zhang et al [76] recently developed a new population-based glycaemic control Markov model that simulates natural variation in HbA1c progression, and showed that when metformin monotherapy was intensified with SUs, DPP-4 inhibitors, GLP-1 receptor agonist or insulin, all regimens resulted in similar life-years and quality-adjusted life-years, regardless of the glycaemic control goal.Both pooled analysis and randomized clinical trials confirm that DPP-4 inhibitors provide a reasonable therapeutic alternative for elderly people with diabetes, as they lead to a significant improvement in glycaemic control, have a safety profile that is similar to placebo, are potentially better tolerated with respect to metformin, and are associated with a low risk of hypoglycaemia at least while used in monotherapy or in combination with insulin sensitizers. This view has also been confirmed by the results of the meta-analysis carried out by Schwarz [77].…”
mentioning
confidence: 99%
“…Another analysis performed on 39 randomized controlled trials involving 17 860 individuals, showed that glucagon-like peptide-1 (GLP-1) analogues led to a greater decrease in HbA1c compared with SUs, glinides, thiazolidinediones, α-glucosidase inhibitors and DPP-4 inhibitors [75]. Aiming to assess the benefits and harms of commonly used antihyperglycaemic treatment regimens, Zhang et al [76] recently developed a new population-based glycaemic control Markov model that simulates natural variation in HbA1c progression, and showed that when metformin monotherapy was intensified with SUs, DPP-4 inhibitors, GLP-1 receptor agonist or insulin, all regimens resulted in similar life-years and quality-adjusted life-years, regardless of the glycaemic control goal.Both pooled analysis and randomized clinical trials confirm that DPP-4 inhibitors provide a reasonable therapeutic alternative for elderly people with diabetes, as they lead to a significant improvement in glycaemic control, have a safety profile that is similar to placebo, are potentially better tolerated with respect to metformin, and are associated with a low risk of hypoglycaemia at least while used in monotherapy or in combination with insulin sensitizers. This view has also been confirmed by the results of the meta-analysis carried out by Schwarz [77].…”
mentioning
confidence: 99%
“…We are grateful for the comments from Messori and Bellia (1) and those of Bae et al (2) regarding our article (3). We hope the following response will clarify the questions they raised.…”
Section: Response To Comments On Zhang Et Almentioning
confidence: 82%
“…However, the cost of this benefit was less in patients who were treated with sulfonylureas. 22 These drugs were also associated with a longer interval until insulin was required than was the case when other oral agents were used. These findings are being translated into potential revisions of guidelines used by care providers.…”
Section: Expanding Through Research Translation and Innovationmentioning
confidence: 99%